Determinants of food status and maternal technology and their effects on the growth of recently weaned children in rural West Province (Cameroon) - Gwanfogbe, Philomina Ndawoh (Kansas State University, 1994)
Knowledge of the household food security of a community is necessary for understanding nutritional status of individuals and for effective policy planning. Food status of 300 rural households in West Province, Cameroon, with children between 15 and 36 months of age was studied. Most (47.9%) of the households were low food secure, 36.3% moderately food secure, and only 16.6% highly food secure. Household food security was positively correlated (p $<$ 0.05) with total number of food crops grown; total number of days per week food crops were eaten; total number of days per week fruits, green leafy vegetables and other vegetables were eaten; and negatively correlated (p $<$.0000) with total number of food crops bought by households. Malnutrition still exists in the rural areas of the West Province of Cameroon. We observed that 27% of the children were stunted, 17.3% wasting, and 0.3% acutely undernourished. Household food security as measured did not independently influence growth status (chronic or wasting) of children, although it interacted with other variables to explain differences in undernutrition. Household food consumption practices (variety and frequency of eating various foods), good hygienic and health practices, and weaning ages of children were associated with reduced stuntedness. Interaction among variables indicated that areas of maternal technology such as mothers experience, physically assisting the child at meals, and preparing and serving various foods frequently contributed positively to good growth of children. There were more children (36.7%) with good growth in low food secure households (positive deviants) than there were stunted children (4.7%) in high food secure households (negative deviants). More mothers of positive deviant children left their children with other people at an older age, had better hygienic practices, and served food to their children before themselves than mothers of negative deviant children. Because some culturally acceptable practices such as quality of dirt disposal, age at which mother started leaving the child at home, serving position of the child, mothers' experience, physically assisting the child at meals, frequently preparing and serving various food, and washing of hands were found to be different in households with adequately nourished and poorly nourished children these areas can be emphasized in nutrition education and intervention programs.
Keywords: Nutrition; Public health